GAUTIER H.A JUYNBOLLâS PERSPECTIVE ON âADÄLAá¸¦ AL-á¹¢Aá¸¤ÄBAH - Wafi, Mahmud (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2018)
á¹¢aá¸¥Äbaá¸§ is the first generation who believe to the Prophet Muá¸¥ammad [p.b.u.h] and accepted the teachings of IslÄm (the á¸¥adÄ«ts of the Prophet) directly from Him. They are very obedient to the Prophet so that they may not dare to betray and lie intentionally in the narration of á¸¥adÄ«ts. They are âadil generally. Muslims believe that whole companions have âadÄlaá¸§ quality, which is famous by a dictum: kullu á¹£aá¸¥Äbaá¸§ âudÅ«l. Furthermore, this belief has come as something approved theologically. This concept becomes stronger when the hadith criticism, traditional scholars are more oriented sanad which has implications for the placement of narrators personality in a position that can not be ignored. This is clearly different from Juynboll, he is one of the Orientalists who came from Netherland who developed the theory of common linkThe conclusion of this research that Juynboll denies the method of hadith criticism. He claims that this theory occurred in the evolutive schema, and is the creation of muá¸¥addits. On the other hand, the author views that the denial of Juynboll for collective taâdÄ«l is one of the instruments to strengthen the theory of common link.